2008
DOI: 10.1016/s1808-8694(15)31373-2
|View full text |Cite
|
Sign up to set email alerts
|

Otorhinolaryngological and esophageal manifestations of epidermolysis bullosa

Abstract: EB is a rare disease and patients must be sent for treatment at reference centers. Physicians treating patients for EB must be aware of the measures required to improve the quality of the treatment provided without putting the patients in harm's way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Strictures and stenoses of the anus, pulmonary artery, nostril, urethra, anterior commissure, pylorus, larynx, and rectum were reported in 0.2% to 15% of patients with RDEB in five studies (Table 1) [22,27,29,30,52]. In two analyses of the US National EB Registry (N = 422-425), the lifetime cumulative risk of esophageal strictures was much higher than risk of laryngeal stenoses and strictures (Table 2) [29,30].…”
Section: Strictures and Stenosesmentioning
confidence: 99%
See 3 more Smart Citations
“…Strictures and stenoses of the anus, pulmonary artery, nostril, urethra, anterior commissure, pylorus, larynx, and rectum were reported in 0.2% to 15% of patients with RDEB in five studies (Table 1) [22,27,29,30,52]. In two analyses of the US National EB Registry (N = 422-425), the lifetime cumulative risk of esophageal strictures was much higher than risk of laryngeal stenoses and strictures (Table 2) [29,30].…”
Section: Strictures and Stenosesmentioning
confidence: 99%
“…In three studies of neonates with RDEB, the vast majority of infants developed blisters within one week of birth (range of 70% to 94%; Table 1) [16,33,35]. Five studies reported on the incidence of oral blisters or lesions in patients with RDEB [21,22,33,43,48]. The proportion of patients experiencing these lesions ranged from 79 to 100% [33,43,48].…”
Section: Wound Burdenmentioning
confidence: 99%
See 2 more Smart Citations
“…Fantauzzi et al 1 described auricular localization of this disorder as rare since they reported only 2 cases out of 60 patients.…”
Section: Introductionmentioning
confidence: 99%